A Sentiment Analysis on the Resumption of Icc Investigation on the Philippine Drug War - Obenza, Brandon Nacua; Baradillo, Danilo G. (Research Parks Publishing LLC, 2024)
The purpose of this sentiment analysis study was to explore the Face Threatening Acts (FTAs) on the sentiments of Filipino netizens regarding the resumption of the International Criminal Court (ICC) investigation of the Philippine government's drug war. This study employed qualitative design, specifically corpus linguistics and sentiment analysis. The findings revealed that most of the FTAs found in the sentiments of Filipino netizens are threats to the positive face and negative face of the hearer. The sentiments on the proposal to resume the ICC investigation of the Philippine drug war can be clustered into three essential themes or categories- attitude, call to action, and credibility. Additionally, the majority of the participants- Filipino netizens are negative towards the proposal to continue the investigation on the Philippine Government's war on drugs. Finally, the findings revealed that Filipino netizens employ various face-threatening acts in expressing their sentiments and opposition to the ICC probe on the Philippine drug war, thereby highlighting the intricate interplay of politeness theory in shaping public sentiment on this contentious issue.